2016
DOI: 10.4103/0019-5154.190132
|View full text |Cite
|
Sign up to set email alerts
|

Generalized morphea following radiotherapy for an intracranial tumor

Abstract: Morphea is a localized scleroderma variety which can be circumscribed or generalized and is characterized by sclerotic plaques developing on trunk and limbs. Surgery and radiation have been implicated as etiological factors for the development of morphea. Majority of the radiation-induced morphea cases have occurred in patients with breast cancer. The affected areas have been generally restricted to the area of radiation and nearby surrounding area in most of the reported cases. We hereby report a case of a 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In 2017, Caccavale, Caccavale, and La Montagna () analyzed the clinical case, reported by Balegar, Mishra, Chatterjee, Kumari, and Tiwary (), of a 27‐year‐old male who developed radiation‐induced morphea, arising in previously irradiated area, some months after the last cycle of radiotherapy for an intracranial tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Caccavale, Caccavale, and La Montagna () analyzed the clinical case, reported by Balegar, Mishra, Chatterjee, Kumari, and Tiwary (), of a 27‐year‐old male who developed radiation‐induced morphea, arising in previously irradiated area, some months after the last cycle of radiotherapy for an intracranial tumor.…”
Section: Discussionmentioning
confidence: 99%
“…RIM generally occurs within the radiation field but rarer cases demonstrate involvement beyond the treated area ( Akay et al, 2010 , Spalek et al, 2015 ). There are a few reported cases of distant site morphea in response to radiation therapy ( Ardern-Jones and Black, 2003 , Balegar et al, 2016 ). One case of endometrial cancer that was treated with brachytherapy and external beam radiation therapy featured lesions that extended from the site of treatment to the right lower abdomen and the upper and lower leg ( Akay et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…I am delighted that authors have shown keen interest in the case report published in the journal. [ 1 ] Radiation in our case definitely caused alteration in the local immune response the so-called “immunocompromised cutaneous district,” which led to the development of morphea. The authors have thrown light on the mechanism, by which immune dysregulation occurs in the irradiated areas.…”
mentioning
confidence: 82%